The Use of High Pressure Grinding Rolls for Crushing Magnetite (The Australasian Institute of Mining and Metallurgy, 2009)
The paper describes data from test work programs on a range of magnetite ores in Australia and overseas. The analysis looks at the behaviour of material of different sizes fed to the rolls and the change in product size as a result of that, the conclusion being that there is a logarithmic relationship. The paper develops a form of equation to predict the product size from a given feed size distribution. The behaviour of the various magnetite ores is compared to more standard test methods such as crushing work index and unconfined compressive strength.